Contribution of the first national radio channel to media coverage of the Algerian national football team - zouaoui, abdelouahab; mendjhi, makhlouf; bouslah, nadir (Journal of Social Sciences and Humanities, 2021)
The media in general and sports media in particular are important in broadcasting news, information and facts related to the sports field and providing all the information about any competitive sports activity through providing rules and regulations governing games such as football. In Algeria, Algerian radio is an important source of news about the national football team qualifying for the 2019 African Cup of Nations in Egypt. It provides news service to the listener wherever it may be. The news have been associated with radio since its creation, and have evolved with the development of technology of coverage of sports and events, and sports radio media needs no intermediary as the radio message arrives directly from the broadcaster to the listener....